Application of cluster approach to the development of industrial potential: innovative policy and management support - Kuzmin, O.; Stanasyuk, N.; Olikhovska, M. (Lviv Politechnic Publishing House, 2017)
In modern conditions, the role of industrial potential is increasing, which will ensure the modernization of the national economy. The emergence of crisis phenomena of clusterization in the industrial sector of the state is deepening due to the lack of directions in the management of its development. Therefore, the purpose of our article is to study the peculiarities and benefits of using the cluster approach in the management of industrial potential, to identify the main disadvantages of domestic clustering, taking into account foreign experience, and to elaborate of proposals for the development of industrial clusters in Ukraine. The article deals with the economic interpretation of the term ”cluster” and highlights the main characteristics and factors of the cluster problem presented in the scientific papers of scientists. The authors ground the main advantages of the cluster approach to the development of industrial potential and identify the main obstacles to the successful application of clustering in Ukraine. The relationship between the benefits and results of the application of the cluster approach for the formation of innovation-industrial policy in the state is established. During the research, the world experience in applying the cluster policy mechanism has been studied, and the directions of state support in the formation of favourable conditions for the development of clusters in industry have been proposed.
Keywords: cluster; cluster approach; clustering; industrial cluster; industrial potential; 330.341.1